Distribution of Dust Color Temperature, Planck’s Function, and Dust Mass around PSR J1240-4124 - Chaudhary, Ashok; Thapa, Bikash; Sodari, Tapendra; Chaudhary, Keshab; Upadhyay, Devendra Raj (Journal of Nepal Physical Society, 2022)
The dust properties in the interstellar medium play an important role in structure formation and extinction of highenergy radiation. This study performed an investigation of the physical properties like distribution of dust color temperature, Planck’s function, and dust mass of the cavity around the pulsar PSR J1240-4124 in the IRIS and the AKARI surveys. In our study, the dust color temperature in the IRIS survey is found to be in the range of 23.607 ± 0.012 K to 24.342 ± 0.012 K with an offset of 0.735 K. Such low offset temperature indicates that the isolated cavities are in thermal equilibrium. In the case of the AKARI survey, the dust temperature was found to be in the range of 16.123 ± 0.017 K to 18.802 ± 0.017 K with an offset of 2.679 K. The average dust mass in IRIS survey is found to be 2.1 × 10−4 M⊙ and that of the AKARI is 8.1× 10−4 M⊙. The size of the structure in the IRIS map is 14.62 pc × 6.24 pc and that of the AKARI map is 5.80 pc × 0.17 pc. The angle of inclination for the selected cavity region is found to be 73.330° in IRIS and that of AKARI is 110.260° . We have tried to present the relationship among the different physical parameters and compare the results in the IRIS and the AKARI surveys. Our findings are similar to those obtained in previous studies of other cavity structures around pulsars. This confirms the validity of the existing results for a new cavity around PSR J1240-4124.